2019
DOI: 10.3389/fpsyg.2019.00252
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Effects of Seeing Green Environment on Psychophysiological Parameters When Walking or Running

Abstract: Several studies have investigated the influence of perceiving colors on affective outcomes and/or performance. However, the effects of seeing colors on self-selected behaviors have received little attention from physiologists and psychologists. Therefore, the present study aimed at examining whether exposure to green and red environments could influence affective judgments, perception of effort, heart rate, and gait speeds when walking and running at a self-selected pace. Participants were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 63 publications
2
21
0
1
Order By: Relevance
“…The positive responses could be attributed to the association between green color and nature, grass, and trees and remind observers both outside and spring. The results of the study seem to support that seeing green plants can have relaxing effects for the Japanese as appeared by decreasing Oxy-Hb in the feeling area and might affect the motor skill for Egyptians as demonstrated by increased Oxy-Hb in the motor area [53,54]. Previous studies showed that green color was the most efficient color for mental comfort [55,56].…”
Section: Discussionsupporting
confidence: 59%
“…The positive responses could be attributed to the association between green color and nature, grass, and trees and remind observers both outside and spring. The results of the study seem to support that seeing green plants can have relaxing effects for the Japanese as appeared by decreasing Oxy-Hb in the feeling area and might affect the motor skill for Egyptians as demonstrated by increased Oxy-Hb in the motor area [53,54]. Previous studies showed that green color was the most efficient color for mental comfort [55,56].…”
Section: Discussionsupporting
confidence: 59%
“…As speculated previously, visual experience might play an important role in green walking [ 30 ]. A simulation by Briki and Majed [ 31 ] has confirmed the calming and relaxing effect of the color green on the human organism, which further implied the importance of visual interacting with plants during green walking. As the night went on, though considerable lights were placed in the green space, the illumination situation was still the worst due to the shading of tree crowns ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, visual experience plays an important role in green walking [ 30 ], and greenness of plants can help to achieve positive changes in physical and mental indices [ 31 ]. Therefore, improper lighting at night may interfere with the cognition of greenness and thus reduce the effects from natural elements.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the experimenters asked the two experts to use either the color white or the color gray (which are achromatic colors) as jersey colors of the two teams. We avoided chromatic colors, such as red, blue, or green, since studies evidenced that such colors could influence affective judgments and physiological states (e.g., Recours and Briki, 2015; Briki and Hue, 2016; Briki and Majed, 2019). Furthermore, the experimenters demanded that TBP simulations would contain only passes, which had to be carried out in a diversity of directions in the region of the center circle of the football pitch (see Figure 2).…”
Section: Methodsmentioning
confidence: 99%